Cloning and analysis of LFY-like gene from Citrus - LIU Shu-fang; CHEN Li-geng; CHEN Da-ming; XU Chang-jie (浙江大学学报. 农业与生命科学版)
The homologous DNA fragment of LFY was cloned from citrus genomic DNA that had been isolated from Sweet orange (Citrus sinensis (L) Osbeck) using Uneven PCR. Analysis of the nucleotide sequence indicated that homology was up to 90% between it and NFY, another LFY-like gene, which implied that they were highly conserved on their structure.